A critique of thé sustainable development concept - a statement - Drummond, Jose Augusto (Sustainability in Debate, 2024)
The text contains a critique of the concept of sustainable development and of the field of sustainability, pointing out its logical, ethical and scientific inconsistencies for the study of environmental issues. It also presents authors and concepts that adopt distinct interdisciplinaty approaches to the study these issues.